Relations between rapid speech transmission index (RASTI) and other acoustical and architectural measures in churches - António P. O. Carvalho (1999)
The use of RASTI in churches is studied and the relationships with acoustical and architectural parameters identified using a major survey of Catholic churches in Portugal. It was found that the vast majority of churches tested have RASTI values below 0.45 giving a poor rating in the quality of speech intelligibility. RASTI values within churches, can be reasonably predicted by the use of Center Time TS at 1000 Hz. Loudness (L) does not appear as an important characteristic regarding RASTI values supporting the idea that the intelligibility of speech, under reverberant conditions does not depend on Loudness. A prediction equation using three architectural parameters was calculated to estimate the average RASTI in churches. The effect of the architectural styles and the use of pulpits on RASTI values was also studied.